Utilization of Interactive Learning Media to Improve the Science Learning Outcomes of Students at State Junior High School 1 Huamual Belakang - E. Untajana, Sally; Bayu Prasada Dulhasyim, Ashari; Sopacua, Fryan; Sopacua, Venty (Unram Journal of Community Service, 2025)
Improving the quality of learning is one of the main focuses in the field of education. One factor that plays a role in enhancing students' understanding is the use of interactive learning media. This media allows students to be more active in the learning process, especially in understanding abstract concepts. However, based on interviews with teachers at State Junior High School 1 Huamual Belakang, it was found that the utilization of interactive learning media at that school is still very minimal. Therefore, this Community Service Program (PKM) aims to train teachers in using PhET, Prezi, Seesaw, and Renderforest applications as interactive learning media that can improve student learning outcomes. The method used in this activity is direct instruction, which includes material presentation, demonstrations of application usage, simulations, and discussion and Q&A sessions. The evaluation was conducted through a questionnaire filled out by teachers and students after the training. The analysis results from the questionnaire indicate that the use of interactive learning media received positive feedback from both teachers and students. Teachers felt more assisted in delivering the material, while students found it easier to understand abstract concepts. Thus, this activity has a positive impact on enhancing teachers' skills in utilizing learning technology and helps students understand the material more effectively. This program is expected to be implemented sustainably in other schools to improve the quality of education.